Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1186/1471-2350-13-119
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of single nucleotide polymorphisms in microRNAs (hsa-miR-196a2 rs11614913 C/T) from Brazilian women with breast cancer

Abstract: BackgroundEmerging evidence has shown that miRNAs are involved in human carcinogenesis as tumor suppressors or oncogenes. Single nucleotide polymorphisms (SNPs) located in pre-miRNAs may affect the processing and therefore, influence the expression of mature miRNAs. Previous studies generated conflicting results when reporting association between the hsa-miR-196a2 rs11614913 common polymorphism and breast cancer.MethodsThis study evaluated the hsa-miR-196a2 rs11614913 SNP in 388 breast cancer cases and 388 con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
5

Year Published

2013
2013
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 20 publications
(36 reference statements)
3
35
0
5
Order By: Relevance
“…The article published by Alshatwi contained discrepancies between the data shown in the tables and the data described in the results section [14]; therefore, after consultation with the author, these data were excluded. In Catucci's [19] and Linhares's [28] studies, the genotype frequencies were presented according to the subjects' country or race, as in previous reports [29], [30]; thus in the present analysis each group was considered as an independent study. Moreover, in some included articles, if two or more miRNA SNPs were investigated in an article, each miRNA SNP was considered as an independent study.…”
Section: Resultsmentioning
confidence: 99%
“…The article published by Alshatwi contained discrepancies between the data shown in the tables and the data described in the results section [14]; therefore, after consultation with the author, these data were excluded. In Catucci's [19] and Linhares's [28] studies, the genotype frequencies were presented according to the subjects' country or race, as in previous reports [29], [30]; thus in the present analysis each group was considered as an independent study. Moreover, in some included articles, if two or more miRNA SNPs were investigated in an article, each miRNA SNP was considered as an independent study.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies indicated that miR-196a2C>T polymorphisms have been widely investigated in various cancers, such as non-small cell lung cancer, breast cancer, pancreatic cancer and esophageal cancer as well as gastric cancer (Zhan et al, 2012;Linhares et al, 2012;Pavlakis et al, 2013;Wei et al, 2013;Yuan et al, 2013). Three studies reported that miR-196a2C>T polymorphism are associated with development of HCC (Li et al, 2010;Qi et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The nucleotide change of T to C may affect the miR-196a2 expression (Saunders et al, 2007;Chu et al, 2011). Recent studies show that rs11614913 may influence lung cancer (Tian et al, 2009;Hong et al, 2011;Yuan et al, 2013), breast cancer (Hoffman et al, 2009;Linhares et al, 2012), head and neck cancer (Christensen et al, 2010), hepatocellular carcinoma (Xu et al, 2008;Qi et al, 2010;Hao et al, 2013), gastric cancer (Peng et al, 2010), prostate cancer (George et al, 2011) and others . On the contrary, there are also several studies for both rs2910164 and rs11614913 polymorphisms indicate conflicting results asserting either lack of association or decreased cancer risk (Xu et al, 2011;Hezova et al, 2012;He et al, 2012;Xu et al, 2013;Zhang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%